Living both well and sustainably: a review of the literature, with some reflections on future research, interventions and policy. (13th June 2017) - Kasser, Tim
Abstract : The idea that human well-being (WB) can be supported and even enhanced by using, producing, buying, selling and consuming less 'stuff' is anathema to many living under consumer capitalism. Yet a growing research literature actually finds that frequent engagement in pro-ecological behaviours (PEBs) is positively correlated with personal WB. This paper reviews data relevant to three possible explanations for the apparent compatibility of PEBs and WB: (i) engaging in PEBs leads to psychological need satisfaction, which in turn causes WB; (ii) being in a good mood causes people to engage in more prosocial behaviours, including PEBs; and (iii) personal characteristics and lifestyles such as intrinsic values, mindfulness and voluntary simplicity cause both PEBs and WB. Because each explanation has some empirical support, I close by reflecting on some relevant interventions and policies that could strengthen each of these three pathways and thereby promote living both well and sustainably. This article is part of the themed issue 'Material demand reduction'.